Continuing education of teachers in a teaching unit of the state public network in the city of Santa Helena de Goiás-Goiás: resistance or challenge? (Research, Society and Development, 2021)
This work aims to know the main interferences in the continuing education of teachers from the perceptions of teachers from the Teaching Unit of the State Public Network in the municipality of Santa Helena de Goiás – Goiás. For this, the following specific objectives were established for this work: a) enumerate the participation in continuing education of teachers from the School Unit of the State Public Education Network during the years 2018 and 2019; b) identify the situation of the teacher's workload at the school and its relationship with continuing education; c) verify the participation of teachers in training of teachers in continuing education offered by other institutions. With regard to methodological procedures, this is an exploratory field research with a quantitative approach, carried out with 24 teachers. The data collected through a questionnaire were systematized and analyzed according to a quantitative approach, which allowed us to consider that continuing education is a challenge because it depends on factors related to the teacher, such as intense routine with high workload, lack of salary appreciation and Social; and, elements external to the teacher such as the lack of continuing education offered by the State Department of Education.